2003
DOI: 10.31729/jnma.781
|View full text |Cite
|
Sign up to set email alerts
|

Some Observation on Human Clavicle

Abstract: The present study was done in the human clavicles that were available from department of Anatomy of Nepalgunj Medical College, Chasapani Nepal. Observations were made on length of the clavicle, mid shaft circumference cornoid tubercle Curvature index of the clavicles were also calculated. Results were analysed and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…28 However, it is interesting to note that several studies have shown that the male clavicles are more horizontally curved in relation to female clavicles. [29][30][31] As for the analysis between the genders, tests were done for each antimerism. For the bones on the right side, significant differences were found between the variables clavicle diaphysis circumference (p < 0.01), ML (p < 0.01), weight (p < 0.01), HAE (p < 0.01), WAE (p − 0.028) and for WSE (p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…28 However, it is interesting to note that several studies have shown that the male clavicles are more horizontally curved in relation to female clavicles. [29][30][31] As for the analysis between the genders, tests were done for each antimerism. For the bones on the right side, significant differences were found between the variables clavicle diaphysis circumference (p < 0.01), ML (p < 0.01), weight (p < 0.01), HAE (p < 0.01), WAE (p − 0.028) and for WSE (p < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…The female clavicle is generally less robust than the male clavicle, with less rugosity and muscle attachments (Bilodi et al, ; Murphy, ; Parsons, ; Ray, ; Terry, ). The present study examined the sexual dimorphism of the clavicle and found that all three variables of the clavicle (MAXL, SAGD, VERD) were larger in males than in females in the South African coloured sample; male clavicles were significantly longer (MAXL) than female clavicles and broader for both VERD and SAGD dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the morphology of the clavicle is influenced by factors such as age, sex, biological affinity, and musculature (Black & Scheuer, ; Bilodi, Sinha, & Kumaran, ; Ljunggren, ; Murphy, ; Parsons, ; Ray, ; Terry, ). Overall, the female clavicle is generally less robust than the male clavicle with less rugosity and muscle attachments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation